Revenue Mobilization and Accountability at the Local Government Level: The Voice of the Voiceless - Awineyesema, Abiire; Marfo-Yiadom, Edward; Akurugo Adongo, Joseph; Ayine Adaane, Lawrence (Indonesian Accounting Research Journal, 2024)
This paper examined revenue mobilization and accountability at the local government level using a District Assembly in Northern Ghana. It employed the qualitative approach and used thematic techniques for data processing and analysis. Thirteen participants were sampled purposively for this study. A focus group discussion comprising six participants and seven interviews was conducted. The study revealed that revenue from the exit of goods and market operations form the main source of internally generated funds to the Assembly. It was also revealed that citizens do not know what the assembly uses their revenues for. Finally, it was reported that the assembly did not account for revenues mobilized to the people.This study provides researchers, practitioners, as well as authorities within the public finance landscape of Ghana with pieces of comprehensively detailed information on revenue mobilization and application issues, and might serve as a point of call to higher authorities to take pragmatic steps to address the financial malfeasances in public departments and agencies. It is the first study to have utilized the qualitative approach, anchored in both agency and stakeholder theories, to investigate revenue mobilization and accountability issues in a local government institution. It also brings new insights into the growing discourse in public financial management which is of great concern to the current Auditor General of Ghana, as well as the international community.